AI–Tree HR Model: Tree HR Personality Assessment for Strengthening Garuda Transformation School Human Resources - Amir Tengku Ramly; Zainuddin Iba; Santi Lisnawati; Reni Sinta Dewi (Jurnal Manajemen, 2026)
National education transformation demands the strengthening of human resources (HR) with character, adaptability, and technological literacy. This article develops and tests the AI-Tree HR Model, a digital-based personality assessment system that integrates the HR Tree Personality with artificial intelligence. This model is built on the philosophy of the HR Tree Model (Ramly, 2023), which describes human development through three main structures: roots (values ​​and spirituality), trunk (competence and mindset), and fruit/leaves (behavior and work results). This study uses a Research and Development (R&D) approach with the ADDIE framework and Agile Software Development principles. The research subjects consisted of 582 respondents (teachers, students, and principals) in a school environment who participated in the digital assessment based on the AI-Tree HR Personality System. Analysis was conducted using the Multi-Stage Weighted Index (MSWI) method on three main dimensions: ease of use, usability, and accuracy. The results show that the AI-Tree HR Personality system has high content validity and excellent reliability, with a total feasibility index of 92.7% (very feasible). AI integration improves the accuracy of assessment results, provides adaptive learning recommendations, and accelerates the process of mapping the character and potential of educators and students. Conceptually, this research expands the paradigm of local human resources, which are based on values ​​and spirituality, with the support of AI technology. Practically, the implementation of the AI-Tree HR Model will strengthen Garuda School's position as a model for national education transformation based on character, values, and technology towards the vision of Golden Indonesia 2045.